The Effectiveness Of Aluminum Foil Swaddling On Increased Body Temperature Of Newborns At The Midwife's Independent Practice Sulistyo Rahayu Central Lampung - Prasetyowati Prasetyowati; Gangsar Indah Lestari; Islamiyati Islamiyati (The International Science of Health Journal, 2023)
Newborns lose heat 4 times more than adults. This heat loss causes a drop in temperature. In the first 30 minutes the temperature drops between 3-4 degrees Celsius. In addition, the body's heat regulation center is not functioning perfectly, which makes it easier for babies to lose heat through evaporation, radiation conduction, or conventions and cold temperatures in the environment where babies are born can make babies hypothermic. The initial survey conducted at PMB Sulistyo Rahayu in 2021 found 158 deliveries with an average monthly delivery of between 13-15 deliveries, and the number of newborns with mild hypothermia was 11 babies. The treatment for hypothermic babies at TPMB Sulistyo Rahayu uses the kangaroo method and cloth swaddles. The purpose of this study was to determine the effectiveness of using aluminum foil swaddles in increasing the baby's body temperature. This research is a quantitative research, with an experimental study method with a pretest-posttest research design with a control group. The sample in this study was 36 babies using simple random sampling technique. The results of the study showed that the use of aluminum foil swaddles increased the baby's body temperature more effectively than cloth swaddles (p value = 0.000). The results of this study are expected to provide output in the form of articles in Sinta accredited journals and instant aluminum foil swaddles that can be used by midwives to treat hypothermia in newborns at the Mandiri Midwife Practice.